Pseudocapacitance‐Induced Synaptic Plasticity of Tribo‐Phototronic Effect Between Ionic Liquid and 2D MoS 2 - Ahmadi, Ribwar; Abnavi, Amin; Hasani, Amirhossein; Ghanbari, Hamidreza; Mohammadzadeh, Mohammad Reza; Fawzy, Mirette; Kabir, Fahmid; Adachi, Michael M. (Small (Weinheim an der Bergstrasse, Germany), 2024)
Contact‐induced electrification, commonly referred to as triboelectrification, is the subject of extensive investigation at liquid–solid interfaces due to its wide range of applications in electrochemistry, energy harvesting, and sensors. This study examines the triboelectric between an ionic liquid and 2D MoS 2 under light illumination. Notably, when a liquid droplet slides across the MoS 2 surface, an increase in the generated current and voltage is observed in the forward direction, while a decrease is observed in the reverse direction. This suggests a memory‐like tribo‐phototronic effect between ionic liquid and 2D MoS 2 . The underlying mechanism behind this tribo‐phototronic synaptic plasticity is proposed to be ion adsorption/desorption processes resulting from pseudocapacitive deionization/ionization at the liquid–MoS 2 interface. This explanation is supported by the equivalent electrical circuit modeling, contact angle measurements, and electronic band diagrams. Furthermore, the influence of various factors such as velocity, step size, light wavelength and intensity, ion concentration, and bias voltage is thoroughly investigated. The artificial synaptic plasticity arising from this phenomenon exhibits significant synaptic features, including potentiation/inhibition, paired‐pulse facilitation/depression, and short‐term memory (STM) to long‐term memory (LTM) transition. This research opens up promising avenues for the development of synaptic memory systems and intelligent sensing applications based on liquid–solid interfaces.